Islam dan HAM: perdebatan mencari titik temu - Ngainun Naim (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
The purpose of this article is explain about how to find common ground between Islam and humanrights. Islam and human rights have a common ground in the value equation, freedom, justice andanother fundamental values. However, there are also many differences. Such differences spawned avariety of attitudes among Moslems. Attempt to find common ground more productive than searchingfor a point difference. The writer presented data from the experts within the framework of study thisissue. Such data are presented in other to find common ground of Islam and human rights. Results ofthe study mentions that much more common ground than differences. Point difference is not to beavoided, but reconstructed in the framework of searching for common ground. Through this way,Islam has conformance with the dynamics and development of the times.